Pengaruh Empati Perawat terhadap Loyalitas Pasien melalui Kepuasan Psikologis sebagai Mediasi pada Rumah Sakit Amira Purwakarta - Muhammad Fadhil Basriyansyah; Muhammad Syahrul Ihza; Andryan Mustopa (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The quality of hospital healthcare services is determined not only by the completeness of physical facilities but also by the psychological aspects and empathy provided by medical staff. This study aims to analyze the effect of nurse empathy on patient loyalty, with psychological satisfaction as a mediating variable at Amira Hospital Purwakarta. This type of research is quantitative with an associative approach. The population in this study consisted of all patients who had received treatment at Amira Hospital Purwakarta, with a sample of 200 respondents selected using the purposive sampling technique. Data collection was conducted through the distribution of a structured questionnaire with a 1–5 Likert scale. The data analysis technique applied Multiple Linear Regression Analysis with a mediating variable using the Causal Steps Method. The analysis results show that nurse empathy has a positive and significant effect on patient psychological satisfaction. Furthermore, psychological satisfaction was found to have a positive and significant effect on patient loyalty. The mediation test results prove that psychological satisfaction significantly mediates the effect of nurse empathy on patient loyalty at Amira Hospital Purwakarta. The hospital management is advised to continuously conduct therapeutic communication and empathy management training for nurses to maintain the psychological stability of patients and increase loyalty commitment for future repeat visits.